1992
DOI: 10.1111/j.1432-1033.1992.tb16981.x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol‐glycan‐specific phospholipase D is an amphiphilic glycoprotein that in serum is associated with high‐density lipoproteins

Abstract: Phosphatidylinositol (Ptd1ns)-glycan-specific phospholipase D was purified from bovine and human serum by phase separation in Triton X-114 and by chromatography on DEAE-cellulose, octylSepharose, concanavalin-A -Sepharose, and hydroxyapatite. The purification of the two enzymes was approximately 1200-fold with a recovery of 3-5%. Bovine serum contained about 40 pgglml of PtdIns-glycan-specific phospholipase D, about 10 times more than the amount determined in human serum. PtdIns-glycan-specific phospholipase D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(57 citation statements)
references
References 40 publications
4
53
0
Order By: Relevance
“…Despite its high concentration in mammalian serum [214] and relatively wellcharacterized molecular biology [215] and biochemistry [216] the physiological role of GPI-PLD is not clear. In serum, GPI-PLD is associated with HDL and is apparently not active [217]. Initial reports indicated that GPI-PLD was active against GPI-anchored proteins only in the presence of detergent, and was not able to cleave the anchors of proteins in a native membrane context [218].…”
Section: Two Types Of Gpi-specific Phospholipases Gpi-phospholipase mentioning
confidence: 99%
“…Despite its high concentration in mammalian serum [214] and relatively wellcharacterized molecular biology [215] and biochemistry [216] the physiological role of GPI-PLD is not clear. In serum, GPI-PLD is associated with HDL and is apparently not active [217]. Initial reports indicated that GPI-PLD was active against GPI-anchored proteins only in the presence of detergent, and was not able to cleave the anchors of proteins in a native membrane context [218].…”
Section: Two Types Of Gpi-specific Phospholipases Gpi-phospholipase mentioning
confidence: 99%
“…Twenty-six of the 35 albumin-associated proteins have been previously reported to be potential biomarkers. Of these, nine were observed only in the albumin-enriched fraction, not the albumin-depleted fraction (compare with [44]). Proteins in this category are alpha-2HS-glycoprotein, apolipoprotein AI, ceruloplasmin, interalpha trypsin inhibitor H4, kininogen, apolipoprotein CIII, fibrinogen, retinol-binding protein, and beta thromboglobulin.…”
Section: Biomarker Potentialmentioning
confidence: 99%
“…In mammals, the only purified and well characterized GPIspecific phospholipase is of the D-type (GPI-PLD) producing phosphatidic acid as one of the products. GPI-PLD was originally discovered in serum [2,3] and later in whole brain [4], neurons [5], and cerebrospinal fluid [6], in the islets of Langerhans [7], liver [8,9], liver mast cells [lo], and milk [6]. GPI-PLD has been purified and characterized from serum [6,1 l-131, and its primary sequence is known from bovine liver cDNA [S].…”
Section: Introductionmentioning
confidence: 99%